2022
DOI: 10.1186/s40345-022-00267-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research diagnostic criteria for bipolar illness (CRDC-BP): rationale and validity

Abstract: Background In the 1970 s, scientific research on psychiatric nosology was summarized in Research Diagnostic Criteria (RDC), based solely on empirical data, an important source for the third revision of the official nomenclature of the American Psychiatric Association in 1980, the Diagnostic and Statistical Manual, Third Edition (DSM-III). The intervening years, especially with the fourth edition in 1994, saw a shift to a more overtly “pragmatic” approach to diagnostic definitions, which were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…During 1960s, pioneering research highlighted that manic-depressive illness, as conceptualized by Emil Kraepelin (1856–1926), is not nosologically homogeneous, stressing the differences between the unipolar and bipolar course of affective disorders in terms of genetics, premorbid personality, and clinical outcomes (Angst & Marneros, 2001 ). Bipolar disorder (BD) is a multidimensional condition which includes a multitude of clinical subtypes (Ghaemi et al, 2022 ; McIntyre et al, 2022 ) and might be based on different neurobiological underpinnings (Han, De Berardis, Fornaro, & Kim, 2019 ; Sepede et al, 2020 ). Over the years, the diagnostic concept of unipolar mania (UM), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During 1960s, pioneering research highlighted that manic-depressive illness, as conceptualized by Emil Kraepelin (1856–1926), is not nosologically homogeneous, stressing the differences between the unipolar and bipolar course of affective disorders in terms of genetics, premorbid personality, and clinical outcomes (Angst & Marneros, 2001 ). Bipolar disorder (BD) is a multidimensional condition which includes a multitude of clinical subtypes (Ghaemi et al, 2022 ; McIntyre et al, 2022 ) and might be based on different neurobiological underpinnings (Han, De Berardis, Fornaro, & Kim, 2019 ; Sepede et al, 2020 ). Over the years, the diagnostic concept of unipolar mania (UM), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the paper by Ghaemi et al ( 2022 ) entitled “Clinical research diagnostic criteria for bipolar illness (CRDC-BP): rationale and validity” recently published in the International Journal of Bipolar Disorders. Essentially the authors highlight the need for “new, purely research-based diagnostic criteria aimed primarily at validity” as “essential to the success of biological and pharmacological research”.…”
mentioning
confidence: 99%
“…The dimension of nonpathological affective temperaments—historically included in the “borderland” described by Akiskal (1994) and recently classified by the CRDC-BP (Ghaemi et al, 2022)—in which the opposite polarities were represented by dysthymic and hyperthymic temperaments;…”
mentioning
confidence: 99%
“…Thus, although not explicitly classifying UM, they implicitly considered the possibility that it might exist. Moreover, the Clinical Research Diagnostic Criteria for Bipolar Illness (CRDC-BP) (Ghaemi et al, 2022) defined UM as the occurrence of manic or mixed manic episodes at least once in a lifetime, without any history of depressive episodes. Scientific literature reported that at least 2 or 3 manic episodes in the absence of depressive episodes, in a period of at least 4 or 5 years, are required for UM diagnosis (even if, according to even more conservative definitions, at least 4 episodes, in a considerably longer period of 10 years, would be needed) (Baek et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation